Efektivitas penerapan media wordwall dalam pembelajaran bahasa arab di MI Syihabuddin Malang - Najya, Shoffany Mafaza (Maliki Interdisciplinary Journal, 2025)
This research aims to describe the effectiveness of using Wordwall as a learning media in Arabic language instruction at MI Syihabuddin Malang. The study was initiated based on the observation that Sstudents' interest and motivation in learning Arabic remained low due to monotonous and less interactive teaching methods. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The findings revealed that the implementation of Wordwall significantly enhanced students’ motivation and classroom engagement. The platform proved to be effective as it presents learning material through enjoyable and accessible interactive games. Wordwall also enabled teachers to deliver lessons in a more dynamic and engaging manner. Thus, Wordwall can serve as an effective alternative media to support Arabic vocabulary acquisition and language skills development among primary school students.